“Waitlist mortality” is high for myeloma patients with limited access to BCMA therapy - Ahmed, Nausheen; Wesson, William; Mushtaq, Muhammad Umair; Bansal, Rajat; AbdelHakim, Haitham; Bromert, Sarah; Appenfeller, Allison; Ghazal, Batool Abu; Singh, Anurag; Abhyankar, Sunil; Ganguly, Siddhartha; McGuirk, Joseph; et al. (Frontiers in Oncology, 2023)
Background The first-in-class approved BCMA CAR-T therapy was idecabtagene vicleucel (ide-cel), approved in March 2021, for RRMM patients who progressed after 4 or more lines of therapy. Despite the promising outcomes, there were limited apheresis/production slots for ide-cel. We report outcomes of patients at our institution who were on the “waitlist” to receive ide-cel in 2021 and who could not secure a slot. Methods We conducted a retrospective review of RRMM patients evaluated at the University of Kansas Cancer Center for ide-cel from 3/2021-7/2021. A retrospective chart review was performed to determine patient and disease characteristics. Descriptive statistics were reported using medians for continuous variables. Survival analysis from initial consult was performed using Kaplan-Meier Survival estimator. Results Forty patients were eligible and were on the “waitlist” for CAR-T. The median follow-up was 14 months (2-25mo). Twenty-four patients (60%) secured a production slot and 16 (40%) did not. The median time from consult to collection was 38 days (8-703). The median time from collection to infusion was 42 days (34-132 days). The median overall survival was higher in the CAR-T group (NR vs 9 mo, p<0.001). Conclusion(s) Many patients who were eligible for ide-cel were not able to secure a timely slot in 2021. Mortality was higher in this group, due to a lack of comparable alternatives. Increasing alternate options as well as improvement in manufacturing and access is an area of high importance to improve RRMM outcomes.